2022
DOI: 10.1161/jaha.121.023357
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statins for Primary Prevention of Cardiovascular Diseases With Hospitalization for COVID‐19: A Nationwide Matched Population‐Based Cohort Study

Abstract: Background There is little evidence on the relationship between statin use and the risk of hospitalization attributable to COVID‐19. Methods and Results The French National Healthcare Data System database was used to conduct a matched‐cohort study. For each adult aged ≥40 years receiving statins for the primary prevention of cardiovascular diseases, one nonuser was randomly selected and matched for year of birth, sex, residence area, and comorbidities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 103 publications
4
21
1
Order By: Relevance
“…In conclusion, the in vitro data emerging from our study provide useful additional information to dissect the mechanism underlying the potential protective effects of statin use in COVID-19. The results are coherent with the clinical reports published in the last two years that highlighted how statins, usually prescribed in patients with pre-existing cardiovascular disease and then frail patients with high risk of severe disease, protect patients from worse prognoses, ICU admissions, and death [ 41 , 42 , 43 , 44 ]. The understandings of statins’ molecular mechanisms in COVID-19 could have a relevant translational impact on disease management.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In conclusion, the in vitro data emerging from our study provide useful additional information to dissect the mechanism underlying the potential protective effects of statin use in COVID-19. The results are coherent with the clinical reports published in the last two years that highlighted how statins, usually prescribed in patients with pre-existing cardiovascular disease and then frail patients with high risk of severe disease, protect patients from worse prognoses, ICU admissions, and death [ 41 , 42 , 43 , 44 ]. The understandings of statins’ molecular mechanisms in COVID-19 could have a relevant translational impact on disease management.…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, the overall conclusion emerging so far from several meta-analyses is that statins used in COVID-19 patients is associated with improved clinical outcomes and reduced Intensive Care Unit (ICU) admission, mechanical intubation, ARDS, and in-hospital death [ 20 , 40 , 41 , 42 ]. The studies included in these meta-analyses and emerging observational studies [ 43 , 44 ] strongly suggest that statin therapy exerts a protective effect against complications from COVID-19, preventing the worst prognosis. These effects are probably related to the immunomodulatory and anti-inflammatory properties of statins, but it has been also proposed that there is a possible direct inhibitory effect on the key steps of the virus life cycle, including internalization, replication, and virion release [ 13 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-hospitalization statin use was shown not detrimental and not associated with an increased risk of all-cause death, ICU admission, need for invasive mechanical ventilation, and onset of myocardial infarction, transient cerebral ischemic attack, or stroke (adjusted OR, 0.82; 95% CI, 0.60–1.11; p = 0.82) [ 21 ]). Furthermore, accumulating retrospective findings suggested interesting benefits of pre-COVID-19 use or post-COVID-19 diagnosis administration of statins on the outcome, including large cohort studies from China [ 22 ], the US [ 23 ], the UK [ 24 ], Canada [ 25 ], and France [ 26 ], confirming the results of the South Korean registry study [ 1 ]. Reduction in the risk of death (up to 28% as evaluated in 2.9 million patients [ 24 ]) was found.…”
Section: Clinical Studies Investigating the Benefits Of Statins In Co...mentioning
confidence: 54%
“…Additionally, in some studies, benefits on the different outcomes were dissociated, such as in the nationwide Swedish cohort study including 572,695 individuals, which showed a decreased risk of death (HR, 0.86; 95% CI, 0.79–0.95; p < 0.001) but not of ICU admission [ 33 ]. Use of low- and moderate-intensity statins was associated with lowered risk compared with non-statin users (HR, 0.78; 95% CI, 0.71–0.86 and HR, 0.84; 95% CI, 0.80–0.89, respectively) in contrast to high-intensity statins (HR, 1.01; 95% CI, 0.86–1.18) [ 26 ]. All statin molecules reduced the risk of hospitalization, whereas pravastatin, rosuvastatin, and simvastatin, but not atorvastatin and fluvastatin, reduced the risk of death.…”
Section: Clinical Studies Investigating the Benefits Of Statins In Co...mentioning
confidence: 99%